Atividade de compostos naturais e sintéticos contra fungos de interesse médico - Danielle Leticia da Silva (2013)
Curcumin showed activity against several fungi. Despite showing activity against some species, encapsulated curcumin was not more active than the pure compound. Most of the compounds showed fungicidal activity. The combination of curcumin and fluconazole in vitro was indifferent. It was also evaluated the interference of the compounds in biomass and viability of biofilm of Cryptococcus spp. It was found that curcumin is effective in inhibiting the viability of the biofilms in concentrations from 2 to 4 times the minimal inhibitory concentration (MIC), also inhibiting the biomass C. gattii in their MIC. The encapsulated curcumin significantly inhibited biofilm biomass and activity in, at most, twice the MIC. Among the aldimines, GQOB 3E6 and GQOB 3D3 were the most effective in inhibiting the viability of the biofilm, while GQOB 3E3 was less effective. In general, the biomass of biofilm was most sensitive to aldimines, being inhibited most times in their MIC. The aldimine GQOB 3D3 was the least toxic to VERO cells (IC50 >250 g/ml) and were selected for testing in a murine model of cryptococcosis. However, this molecule showed to be toxic to animals. On the other hand curcumin, fluconazole and the combination of both were able to reduce fungal load in the lungs and brains of animals, as well as improving the general state of the same in the behavioral evaluation test. Curcumin, therefore, showed to be a promising agent against cryptococcosis. Further studies are needed to determine the best parameters for its administration.